Modelling Thermal Conductivity Enhancement Of Metallic Oxide-Based Nanofluids Using Dimensional Analysis - B. Kristiawan, B.Kristiawan; Kamal, Samsul; Suhanan, Suhanan; Yanuar, Yanuar (2012)
The objective of the present work is to investigate nanofluids thermal conductivity enhancement using available dimensional analysis modeling for thermal conductivity enhancement of metallic oxide-based nanofluids. Nanofluids are engineered by dispersing nanoparticles into ethylene glycol as base fluid with two-step method. Nanofluid samples were prepared with different percentage ratio of nanoparticle mass to 100 Ml suspension of 0.2, 0.5, 1.0, 1.5, 2.0, and 2.5 (%w/v). The TEM and XRD characterization are used to verify specification data of the observed nanofluid. From this characterization, it is found that metallic oxide nanoparticles used in the present study consist of spherical particles with nominal diameter of 21 nm and 13 nm for TiO2 and Al2O3, respectively. In this present work, available semi correlation of nanofluid thermal conductivity enhancement derived using the Buckingham-pi theorem in which Brownian motion of nanoparticle is considered. The predicted effective thermal conductivity enhancement of nanofluid in this model is compared with the experimental data. The experimental results show that thermal conductivity increases remarkably with increasing volume fraction of nanoparticles. The results show that the predicted thermal conductivity enhancement using dimensional analysis model demonstrates fairly good agreement for TiO2/EG and Al2O3/EG with nanoparticle concentration of 1.0 to 2.5 % w/v.